Spontaneous healing responses detected by cone-beam computed tomography of horizontal root fractures: a report of two cases - Fagundes, Dyana dos Santos; Mendonca, Isabela Lima de; Albuquerque, Maria Tereza Pedrosa de [UNESP]; Azevedo Jacinto Inojosa, Ines de Fatima de (Wiley-Blackwell, 2014)
Horizontal root fractures (HRF) usually affect the anterior teeth as a result of trauma, and generally heal spontaneously, depending on the vitality of the pulp. Diagnosis based on clinical findings, sensitivity tests, and radiographic examination is important to determine the presence of a root fracture and to prevent a root fracture from passing unnoticed. Cone-beam computed tomography (CBCT) has been used successfully for diagnosis and prognosis imaging of root fractures and has proved to be superior to other radiographic methods. This study reports two cases of dental trauma caused by a collision and a sports accident. The patients suffered horizontal root fractures in the maxillary left central incisor and in the mandibular left central incisor. The diagnosis of root fracture was confirmed by cone-beam computed tomography (CBCT) images, which also demonstrated spontaneous healing of the fracture line. The repair occurred by interposition of connective tissue in the former case and by interposition of bone and connective tissue in the latter case. The final diagnoses of both cases were based on CBCT images, indicating the importance of a CBCT examination to reach a firm diagnosis and to follow the healing process of root fracture cases, avoiding unnecessary radical endodontic treatment.
Keywords: horizontal root fracture; radicular cervical third; cone-beam computed tomography; spontaneous healing